FRANCISCO FERRER y GUARDIA: Educação e a imprensa anarcosindicalista – “A PLEBE” (1917- 1919) - Gonçalves, Aracely Mehl (2007)
This study examines the libertarian educational thought propagated in Brazil by the anarchists at the end of the XIX century and beginning of the XX one and analyzes the anarchic periodical "A Plebe" within 1917 to 1919, once the press was considered a tool to the diffusion of their ideals. The theoretical reference that endorsed the research was the historical materialism through readings of Marx and Engels’s works. The bibliographical resources that supported the analysis carried out from this referential was constituted by authors who make references to the educational theory developed by Francisco Ferrer y Guardia; author who was adopted by the anarchists in their schools, as well as his own writings and works of Marxists authors who contextualized the passage of the economical agro exporter model to the industrial one in Brazil. The primary sources which are referent to the analyzed periodical were collected at Edgard Leuenroth Archives at UNICAMP, and at Fundación Francesc Ferrer y Guardia in Barcelona, Spain. The study was divided in three chapters: the first one presents and points out the figure of Francisco Ferrer y Guardia in XIX century Europe, the organization and foundation of his Modern Schools as well as his educational thought known as Rationalist Teaching Education. The second chapter deals with the coming of the European immigrants to Brazil, the conditions of work and life that they found here and to which they were submitted to and also the strike movements organized by the anarchosyndicalists who, besides fighting for working improvements also established schools where the educational theory of Francisco Ferrer y Guardia became the pedagogical thought that represented them. On the third chapter an analysis of the referring articles on education found in the periodical "A Plebe” was carried out, within the period cited before, in order to verify whether Ferrer’s pedagogical thought appears in it and if this periodical took the defense of the proletarian education. In general terms, it was concluded that the periodical "A Plebe” contributed to the unveiling of the ideology imposed by the dominant class during the studied period and was an instrument of propagation of Ferrer’s theory in Brazil, as well as an organizer of laboring struggles and opening of libertarian schools. The research demonstrated that the organization of the libertarian schools by the anarchists, the revolutionary speech of their periodicals as well as the organization of strikes and of unions by them, were acts that led to a modification in the work and study conditions of the population, once , fearful that the common people could lead a revolution, the government hurries and organizes laws to prescribe the working activities and creates schools to the working class , thus suffocating the shout and the laborer anarchist organization in all its aspects.